Фізичні моделі перетворень електричного імпульсу в магнітострикційному перетворювачі - Шаповалов, О. І. (НТУ "ХПІ", 2014)
Показано, що вимірювання рівня рідин магнітострикційним методом засновано на реологічних переходах збуджуючого імпульсу хвилеводу в ультразвукові коливання. Досліджено процеси перетворення струмового імпульсу в енергію електромагнітного поля та вплив на магнітне поле перетворювача. Показано, що зміна електромагнітного поля за довжиною хвилеводу є нелінійною, що впливає на діапазон вимірювального контролю рівня таким методом.

Measurement of liquid mediums magnetostrictive method based on the transformation of the electric pulse excitation of the waveguide of ultrasonic vibrations during the passage of the scope of the magnetic field of permanent magnet located on the surface of a floating liquid medium float. The processes of transformation of the current pulse to the energy of the electromagnetic field and the influence of the magnetic field transducer. It is shown that the change in the electromagnetic field along the length of the waveguide is nonlinear, which affects the measuring range of this control method. Theoretical and experimental study of magnetostrictive controls the level of liquid media shows that the magnetic flux created at the elementary element waveguide defined amplitude current pulse and magnetic penetration magnetostrictive material and its cross section. Problem is to determine how the electromagnetic field changes in the interaction with the magnetic field of a permanent magnet, resulting in a ultrasonic electrical signal.
Physical model transformations electrical pulse in magnetostrictive transducers
Keywords: електрорушійна сила; метод нульового градієнта; теорія реологічних переходів; вимірювання; магнітострикція; магнітна енергія; магнітне поле; струм; magnetostriction method; current; waveguide; ultrasound; magnetic field